2013
DOI: 10.5402/2013/590587
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors Affecting the Success of Cloning, Expression, and Mass Production of Enzymes by RecombinantE. coli

Abstract: E. coli is the most frequently used host for production of enzymes and other proteins by recombinant DNA technology. E. coli is preferable for its relative simplicity, inexpensive and fast high-density cultivation, well-known genetics, and large number of compatible molecular tools available. Despite all these advantages, expression and production of recombinant enzymes are not always successful and often result in insoluble and nonfunctional proteins. There are many factors that affect the success of cloning,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 47 publications
2
54
0
2
Order By: Relevance
“…Using endogenous human exosomes as a proof of concept, we have demonstrated that the purification procedures discovered are scalable-and this can be done cost-effectively by suspension conditioning normally adherent HEK-293 cells-providing excellent starting materials for further biochemical, enzymological, and structural study. Because this approach has significant advantages over in vitro assembly of components heterologously expressed in bacteria, which suffers from innate difficulties in expressing large proteins, the need to coexpress multiple interaction partners, and the lack of endogenous post-translational modifications (Fakruddin et al 2013), we believe it will prove to be of great general utility in the study of macromolecular assemblies.…”
Section: Discussionmentioning
confidence: 99%
“…Using endogenous human exosomes as a proof of concept, we have demonstrated that the purification procedures discovered are scalable-and this can be done cost-effectively by suspension conditioning normally adherent HEK-293 cells-providing excellent starting materials for further biochemical, enzymological, and structural study. Because this approach has significant advantages over in vitro assembly of components heterologously expressed in bacteria, which suffers from innate difficulties in expressing large proteins, the need to coexpress multiple interaction partners, and the lack of endogenous post-translational modifications (Fakruddin et al 2013), we believe it will prove to be of great general utility in the study of macromolecular assemblies.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese hamster ovary (CHO) cells, used for the manufacture of a wide range of heterologous proteins, require a demanding selection process to generate production clones efficiently . This is because the expression level of the heterologous gene is determined by multiple factors, including the strength and efficiency of regulatory sequences directing its transcription and processing into messenger RNA (mRNA), the chromosomal integration site, the copy number, the efficiency of translation as well as specific requirements of the particular protein such as post‐translational assembly and modification steps, and finally, secretion . In this context, promoters and their genetic control elements such as enhancers play an important role in integrating and processing gene expression …”
Section: Introductionmentioning
confidence: 99%
“…Recently, several recombinant therapeutic proteins and industrial enzymes are produced using E. coli expression system ( Table 1 ) (Fakruddin et al, 2013; Spadiut et al, 2014; Mane and Tale, 2015). E. coli , produces recombinant proteins, mainly three different forms such as inclusion body, the secretary as well as soluble forms (Fahnert et al, 2004; Zerbs et al, 2014).…”
Section: Introductionmentioning
confidence: 99%